High-speed running quadruped robot with a multi-joint spine adopting a 1DoF closed-loop linkage - Matsumoto, Ojiro; Tanaka, Hiroaki; Kawasetsu, Takumi; Hosoda, Koh (Frontiers in Robotics and AI, 2023)
Improving the mobility of robots is an important goal for many real-world applications and implementing an animal-like spine structure in a quadruped robot is a promising approach to achieving high-speed running. This paper proposes a feline-like multi-joint spine adopting a one-degree-of-freedom closed-loop linkage for a quadruped robot to realize high-speed running. We theoretically prove that the proposed spine structure can realize 1.5 times the horizontal range of foot motion compared to a spine structure with a single joint. Experimental results demonstrate that a robot with the proposed spine structure achieves 1.4 times the horizontal range of motion and 1.9 times the speed of a robot with a single-joint spine structure.